Multisystem inflammatory syndrome in an adolescent girl presenting as atypical Kawasaki-like illness associated with coronavirus disease-19 - Sadhukhan, Meghmala; Joshi, Ranjit K.; Pahi, Prabin P. (Indian Journal of Child Health, 2021)
During the current pandemic of Coronavirus disease (COVID)-19, multiple cases of a new condition in children have been reported with multisystem involvement associated with severe acute respiratory syndrome coronavirus-2, requiring intensive care admission. The World Health Organization has defined it as multisystem inflammatory syndrome in children and adolescents. Here, we report a similar case of a 15-year-old adolescent who presented with clinical features of Kawasaki-like illness along with multisystem involvement. The echocardiogram suggested the presence of coronary artery dilatation and the patient responded well to Intravenous immunoglobulin. Hence, pediatricians need to be aware of this condition in children with multisystemic involvement and these patients need to be treated as early as possible since they may deteriorate quickly.